Correction: Mercapto-benzothiazolyl based ruthenium(ii) borate complexes: synthesis and reactivity towards various phosphines. Issue 22 (15th May 2019) - Zafar, Mohammad; Ramalakshmi, Rongala; Pradhan, Alaka Nanda; Pathak, Kriti; Roisnel, Thierry; Halet, Jean-François; Ghosh, Sundargopal
Abstract : Correction for 'Mercapto-benzothiazolyl based ruthenium(ii ) borate complexes: synthesis and reactivity towards various phosphines' by Mohammad Zafar, et al., Dalton Trans., 2019, DOI: 10.1039/c9dt00498j.